Is Your Organization Addicted to Outsourcing?. Issue 3 (27th February 2013) - Rieley, James B.; Lyon, Angus
Abstract Managers challenged to reduce expenses may find a solution in identifying the part of the business that costs more than it is delivering and then contracting with an external organization to provide the same services for less money. Sometimes the results are as planned, but when the decision to outsource is made without considering the full spectrum of factors that led the organization to consider outsourcing in the first place, the decision to cut in‐house staff and take on outside help can have serious unplanned consequences, and even lead to a counterproductive cycle of costly outsourcing engagements. © 2013 Wiley Periodicals, Inc.